Kid’s Education and Fun Courseware - Ahmad, Ainul Maulid B.; Aziz, Mu’azah Bt. Md; Abdullah, Wan Mahani Bt.; Amat, Mohd Aswad B. Mushim; Ishak, Mohamad Izril B. (International Journal of Engineering and Technology, 2018)
Kids Education and Fun courseware is a project developed to assist kids and preschool teacher in the phonetic language. Besides, it intended to be an additional tool to kids and preschool teacher use in classroom to expert and interested in phonetic language in more depth. Courseware is development is based on the project objectives that to design requirement of KidsEduFun, to design and develop the KidsEduFun as additional tool in learning and to test and evaluate KidsEduFun of usability testing to solve the problem statement in the project. KidsEduFun is comprises of three stages which are alphabet, phonetic and game. In the first stage, there are related to alphabet, the first step should been taken by kids is to know the alphabet. The user can get the information by clicking the button on the display screen. In the second stage, phonetic is the stage where the user can learn the alphabet sound in phonetic language. In the last stage, the user can try to answer the questions via the game provided to test their understanding. The methodologies that will be used in develop this learning program are ADDIE model. Lastly, KidsEduFun is developed to be used as additional tool to kids and preschool teacher in knowing the phonetic language. Besides that, it is able to attract students to study alphabet and phonetic language with the multimedia elements and essential for education now.